THE COMPARISON OF HEALTH EDUCATION THROUGH TELEHEALTH (WHATSAPP) AND BOOKLET ON HIV/AIDS PREVENTION BEHAVIOR IN PROSPECTIVE BRIDES BASED ON THE HEALTH BELIEF MODEL - Khoirunnisa, Khoirunnisa; Ambarsari, Wulan Novika; Aliarosa, Windasari (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Background : HIV/AIDS is a sexually transmitted disease that is currently a disease with a high prevalence in Indonesia with the majority of sufferers in the age range of 25-49 years old. Health education is one of the primary prevention efforts in suppressing the incidence of HIV / AIDS. Currently, there are many media that can be used in delivering health education such as booklets and telehealth. Objectives : The purpose of this study was to determine the most effective media in providing health education on HIV/AIDS prevention behavior in prospective brides based on the health belief model. Methods : The study method used a type of quantitative study with a quasy-experiment. This study has a total sample of 54 respondents with accidental sampling technique. This study instrument used AHBS (AIDS Health Belief Scale) as a questionnaire. Result : There is a significant difference between health education through telehealth and booklets on HIV / AIDS prevention behavior in prospective brides based on the health belief model through the Mann Whitney statistical test obtained the results of p value (0.000 <0.05). Conclusions : It can be concluded that telehealth media is a fairly effective tool with the resulting N-gain score of 59.8% in delivering health education. Through this research, it is hoped that Religious Affairs Office Cimahi can use telehealth (whatsapp) and booklets as a media for HIV/AIDS health education for prospective brides